In merito alle procedure che permettono di correggere le anomalie mitocondriali del nascituro: questioni etiche e prospettive giuridiche (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Women can produce eggs with a high load of abnormal mtDNA. Those who know they have a disease caused by anomalies in the mtDNA can opt for pre-implantation genetic diagnosis and select for the implantation the embryos without mutations in mtDNA or with the lowest proportion of abnormal mtDNA. Another option is to have a baby using donated eggs. The UK House of Commons recently approved two methods for replacing abnormal mtDNA: maternal spindle transfer and pro-nuclear transfer. In maternal spindle transfer (MST), the genetic material in the nucleus of an egg is removed from the intended mother's egg and transferred into an egg from a donor that has had its maternal spindle removed. The reconstituted egg would then be fertilised by the intended father's sperm and the newly formed embryo implanted into the intended mother. In pronuclei transfer (PNT), the pronuclei from the donor embryo are transferred into the donor embryo, which has had its pronuclei removed. The essay will discuss the main moral objections against the various types of nuclear transfer to prevent mitochondial DNA (mtDNA) disorders: the risks for the baby and for the future generations, the problem related to changing of the germ line and the use of similar techniques for other purposes. Our conclusion is that the two main developed methods for replacing abnormal mtDNA are morally approvable because they allow the child who will be born to have a better quality of the life.
Keywords: bioethics; genetic engineering; human cloning; germ line; mitochondrial disease.